Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Chen, Yu-ru; Sha, Rong-rong; Sun, Xiao-li; Guo, Xing-pan; Yang, Yi (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in a realistic aquatic scenario and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. In addition, metal resistance genes (MRGs) and mobile genetic elements (MGEs) showed downward trends in most treatment groups, and they were significantly related to the ARG abundances. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community was the dominant factor contributed the most to the variation in ARG abundance, followed by dissolved metal ions, MRGs, and MGEs under NP exposure. Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes. Taken together, these findings provide insights into the contributions of the combined effect of Cu- and ZnO- NPs on ARG dissemination in the estuarine environment.